2019
DOI: 10.1111/2041-210x.13241
|View full text |Cite
|
Sign up to set email alerts
|

Joint modelling of multi‐scale animal movement data using hierarchical hidden Markov models

Abstract: Hidden Markov models are prevalent in animal movement modelling, where they are widely used to infer behavioural modes and their drivers from various types of telemetry data. To allow for meaningful inference, observations need to be equally spaced in time, or otherwise regularly sampled, where the corresponding temporal resolution strongly affects what kind of behaviours can be inferred from the data. Recent advances in biologging technology have led to a variety of novel telemetry sensors which often collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…There are multiple approaches for increasing the resolution of behaviors using an HMM framework: a more complicated 4-, 5-, or even 6-state model could fit increasingly nuanced behaviors, for example distinguishing resting from sit-and-wait foraging, which is used frequently by black-footed and grey-headed albatrosses [ 12 , 52 ] and accounts for 35% of prey consumed by grey-headed albatrosses [ 52 ]. Alternatively, one could apply a hierarchical HMMs to classify behavioral states occurring at different time scales [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple approaches for increasing the resolution of behaviors using an HMM framework: a more complicated 4-, 5-, or even 6-state model could fit increasingly nuanced behaviors, for example distinguishing resting from sit-and-wait foraging, which is used frequently by black-footed and grey-headed albatrosses [ 12 , 52 ] and accounts for 35% of prey consumed by grey-headed albatrosses [ 52 ]. Alternatively, one could apply a hierarchical HMMs to classify behavioral states occurring at different time scales [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While they found that all methods performed similarly, they concluded that HMMs provide advantages over other methods given their ability to test the effect of predictor variables on state transition probabilities and because HMMs explicitly model serial autocorrelation [ 26 , 30 , 31 ]. Further, HMMs can incorporate multiple types of data [ 32 , 33 ], a feature that is highly relevant to biologging studies since IMU devices typically record simultaneous data streams from multiple sensors (e.g. accelerometers, magnetometers, gyroscopes).…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest and most flexible HMM packages, depmixS4 (Visser and Speenkenbrink, 2010), can accommodate multivariate HMMs, multiple observation sequences, parameter covariates, parameter constraints and missing observations. Similar to depmixS4 in terms of features and flexibility, momentuHMM (McClintock and Michelot, 2018) can also be used to implement mixed HMMs (DeRuiter et al ., 2017), hierarchical HMMs (Leos‐Barajas et al ., 2017a; Adam et al ., 2019a), zero‐inflated probability distributions (Martin et al ., 2005) and partially observed state sequences. In addition to the R packages presented in Table 2, there are numerous R and stand‐alone software packages that are less general and specialise on particular HMM applications in ecology, as well as general statistical programs with which these types of models can be relatively easily implemented (see Appendix B in Supplementary Material).…”
Section: Implementation Challenges and Pitfallsmentioning
confidence: 99%
“…alternative stable states), or it could simply be used to account for unobservable state dynamics at lower levels of the hierarchy as a component of a larger (non‐Markovian) ecosystem‐level process model. Recent HMM methodological developments such as hierarchical formulations that allow data collection and/or state transitions to occur at multiple temporal resolutions (Fine et al ., 1998; Leos‐Barajas et al ., 2017a; Adam et al ., 2019a), nonparametric approaches avoiding restrictive distributional assumptions (Yau et al ., 2011; Langrock et al ., 2018) and coupled HMMs for interacting state processes associated with different sequences (Sherlock et al ., 2013; Touloupou et al ., 2020) extend our capability to incorporate complex data structures and hierarchical relationships scaled from the individual to ecosystem level.…”
Section: Future Directionsmentioning
confidence: 99%
“…Data were assumed to stem from two behavioral processes, operating on distinct temporal scales: a crude-scale process that identifies the general behavioral mode (e.g., migration), and a fine-scale process that captures the behavioral mode nested within the large-scale mode (e.g., resting, foraging, traveling). Intuitively, the former may persist for numerous consecutive dives, whereas the latter agrees to the more nuanced state transitions at the dive-by-dive level, given the general behavioral mode (Leos Barajas et al, 2017;Adam et al, 2019). Hence, a behavior occurring at the crude time scale can be connected to one of the finite internal states, such that each internal state generates a distinct HMM, the internal states of which in turn are linked to the actual observation at a specific point in time.…”
Section: Introductionmentioning
confidence: 89%